Phase 2 study of chidamide in combination with CAG and venetoclax-azacitidine in older patients with newly diagnosed acute myeloid leukemia - Liu, Qingyang; Yang, Jingjing; Lv, Lei; Zhang, Xiawei; Li, Meng; Xu, Lingmin; Huang, Sai; Jing, Yu; Dou, Liping (Frontiers in Immunology, 2025)
IntroductionOlder patients with acute myeloid leukemia (AML) respond poorly to standard induction therapy. DNA methyltransferases (DNMTs) and histone-deacetylases (HDACs) are key regulators of gene expression in cells and have been investigated as important therapeutic targets. However, their effects remains unclear as induction therapy for AML.MethodsPreviously untreated AML patients aged 60 years and over (N=40) were enrolled into this single arm, open-label, phase 2 study to evaluate the clinical efficacy and safety of chidamide combined with CAG and venetoclax-azacitidine (referred to as CACAG-VEN) in elderly AML patients (ClinicalTrials.gov:NCT05659992). All patients received induction treatment with aclarubicin (10 mg/m2/d on days 1, 3, and 5), azacitidine (75 mg/m2 on days 1–7), cytarabine (75 mg/m2 bid on days 1–5), chidamide (30 mg, twice/week for 2 weeks), and venetoclax (100 mg on day 1, 200 mg on day 2, 400 mg on days 3–14). Granulocyte colony-stimulating factor 5 mg/kg/day was administered.ResultsTheoverall response rate was 97.5%, with a composite complete response (CRc) rate of 85.0% after one cycle of CACAG-VEN. Patients with adverse risk according to the ELN guidelines had CRc rates of 81.3%. No patients experienced early death within 30 days of therapy initiation. Grade 3 - 4 non-hematological adverse events included febrile neutropenia in 15 (37.5%) of 40 patients, pneumonia in three (7.5%), sepsis in two (5.0%) and blood bilirubin increase in one (2.5%). The 12-month overall survival rate was 73.4% (95% CI: 55.9–84.8%). The median time to recovery was 15.0 (IQR 10.0-19.5) days for platelets ≥ 20000/mL and 13.0 (IQR 10.5-17.0) days for an absolute neutrophil count ≥ 1000 cells/mL after induction therapy.DiscussionIn conclusion, chidamide in combination with CAG and venetoclaxazacitidine was effective and well tolerated in elderly patients with AML.Clinical trial registrationhttps://www.clinicaltrials.gov/, identifier NCT05659992.